IMPACT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: ACOMPARATIVE STUDY OF CEYLINCO INSURANCE COMPANYLIMITED AND JANASHAKTHI INSURANCE PLC IN VAVUNIYA DISTRICT - Udeshini, R.; Pushpanathan, A. (ZENITH, 2013)
This study attempts to analyze the customer satisfaction and service quality, and the relationship between them of insurance companies, and to identify the approaches to improve the customer satisfaction and the service quality of the insurance companies. The insurance is considered as auxiliary service in the business environment. The main objective of this study is to compare the service quality and customer satisfaction between the Janashakthi Insurance PLC and Ceylinco Insurance Company Ltd in Vavuniya District. This study utilized 50 customers from each insurance company in Vavuniya district. The Exploratory Factor Analysis (Principle Componentwith Varimax rotation) of independent variable such as tangible, reliability, responsiveness, assurance and empathy were measured by using the SPSS package. Then the regression results of independent and dependent variables were measured by structural equation model using the AMOS (Analysis of Movement Structure).
Keywords: Tangible; Reliability; Responsiveness; Assurance; Empathy; CustomerSatisfaction